Discs large regulates somatic cyst cell survival and expansion in Drosophila testis - Papagiannouli, Fani; Mechler, Bernard (Cell research, 2009)
Gonad development requires a coordinated soma-germline interaction that ensures renewal and differentiation of germline and somatic stem cells to ultimately produce mature gametes. The Drosophila tumour suppressor gene discs large (dlg) encodes a septate junction protein functioning during epithelial polarization, asymmetric neuroblast division, and formation of neuromuscular junctions. Here, we report the role of dlg in testis development and its critical function in somatic cyst cells (SCCs). In these cells dlg is primarily required for their survival and expansion, and contributes to spermatocyte cyst differentiation. Cell death primarily occurred in SCCs at the end of spermatogonial amplification at a time when Dlg becomes restricted in wild-type (wt) testes to the distal somatic cells capping the growing spermatocyte cysts. RNAi depletion of dlg transcripts in early SCCs fully prevented testis development, whereas depletion in late SCCs resulted in a breakdown of spermatocyte cyst structure and germ cell individualization. Specific dlg expression in SCCs resulted in developmental rescue of dlg mutant testes, whereas its expression in germ cells exerted no such effect. dlg overexpression in wt testes led to spermatocyte cyst expansion at the expense of spermatogonial cysts. Our data demonstrate that dlg is essentially required in SCCs for their survival, expansion, and differentiation, and for the encapsulation of the germline cells.
Gesehen am 01.08.2017